2009
DOI: 10.1159/000227292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urinary S100B Protein Level and Lactate/Creatinine Ratio for Early Diagnosis and Prognostic Prediction of Neonatal Hypoxic-Ischemic Encephalopathy

Abstract: Background: Early identification and prevention of hypoxic-ischemic encephalopathy (HIE) in newborns may reduce neonatal mortality and neurological dysfunction. Objective: To analyze the diagnostic and prognostic values of urinary S100B level and lactate/creatinine ratio in newborns with HIE. Methods: Seventy-eight full-term newborns with HIE and 25 normal newborns were enrolled. The Neonatal Behavioral Neurological Assessment (NBNA) and Developmental Screening Test were scored. The concentration of urinary S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 17 publications
(11 reference statements)
1
19
0
7
Order By: Relevance
“…Eight of these metabolites are novel markers of perinatal asphyxia (Tables 2 and 3). Lactate and creatinine are currently the two primary metabolites used clinically to assess the degree of hypoxic-ischemic injury due to perinatal asphyxia [43]. Our findings are consistent with the existing literature for these two compounds, and add novel biomarkers that may be clinically important.…”
Section: Discussionsupporting
confidence: 87%
“…Eight of these metabolites are novel markers of perinatal asphyxia (Tables 2 and 3). Lactate and creatinine are currently the two primary metabolites used clinically to assess the degree of hypoxic-ischemic injury due to perinatal asphyxia [43]. Our findings are consistent with the existing literature for these two compounds, and add novel biomarkers that may be clinically important.…”
Section: Discussionsupporting
confidence: 87%
“…Of importance, many of these markers were investigated before the introduction of therapeutic hypothermia [24,25]. At present we still lack a biomarker that could early identify infants at risk for brain injury, especially those with mild or moderate HIE.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of S100B levels in urine has also been used in perinatal medicine as a means to obtain a noninvasive diagnostic tool. Thus, urine S100B concentrations have been shown to be correlated with gestational age in healthy preterm and term newborns (Gazzolo et al 2001c), and urine S100B concentrations at birth have been shown to be significantly higher in preterm newborns developing IVH and/or brain damage (Gazzolo et al 2001b(Gazzolo et al , 2003dLiu et al 2010). They have also been shown to be a valuable predictor of early neonatal death in preterm and full-term asphyxiated newborns (Gazzolo et al 2005a(Gazzolo et al , 2009.…”
Section: S100b In Perinatal Medicinementioning
confidence: 99%